Efektivitas Konseling Kelompok Tekhnik Cognitive Restructuring Untuk Meningkatkan Konsep Diri Siswa di SMK Negeri Singaraja - Megawati Ricky; I Ketut Gading; Putu Ari Dharmayanti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study expects to decide the viability of the Mental Rebuilding Gathering Directing strategies to further develop understudies' reasoning power. The study's design included a brief assessment and a group-control plan for the pre-test. The number of inhabitants in this review were understudies of class XI Friendliness SMK N 1 Singaraja what's more, a sum of 3 classes. Examining was finished through purposive testing. The students in class XI-PH 7, which served as the experimental class and the control class, were the members of the sample. The SPSS 25.0 Windows program was utilized for the t test and Effect Size data analysis techniques. Data The questionnaire is a self-concept questionnaire, so this study uses one of them to improve students' self-esteem through cognitive rehabilitation.concept in Singaraja at SMK N 1. In view of the finishes of this study one might say furthermore, this sort of counsel is powerful. The aftereffects of this study got t = 19.53 Responsiveness = 10.15 p > 0.05, one might say that Ha and Ho are dismissed.